Inglorious empire : what the British did to India - Tharoor Shashi (Hurst & Company, 2017)
Présentation de l'éditeur : "In the eighteenth century, India s share of the world economy was as large as Europe s. By 1947, after two centuries of British rule, it had decreased six-fold. Beyond conquest and deception, the Empire blew rebels from cannon, massacred unarmed protesters, entrenched institutionalised racism, and caused millions to die from starvation. British imperialism justified itself as enlightened despotism for the benefit of the governed, but Shashi Tharoor takes on and demolishes this position, demonstrating how every supposed imperial gift from the railways to the rule of law was designed in Britain s interests alone. He goes on to show how Britain s Industrial Revolution was founded on India s deindustrialisation, and the destruction of its textile industry. In this bold and incisive reassessment of colonialism, Tharoor exposes to devastating effect the inglorious reality of Britain s stained Indian legacy."
Keywords: Inde 1765-1947 (Occupation britannique)